Rol' navyka psichoemocional'noj samoreguljacii v processe adaptacii sportsmenov k uslovijam smeny casovych pojasov - Kozlovskij, A. P.; Kalinkin, L. A.; Morozov, V. N.; Skomorochov, A. A.; Eršov, V. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The paper presents an assessment of the effectiveness of the use of respiratory exercises as a means of restoring athletes with musculoskeletal injuries involved in bullet shooting. Functional capabilities of the respiratory system of shooters with locomotor apparatus damage were studied. The hypoxic load tolerance was assessed. The improvement of the functional capabilities of respiratory system of shooters with the defeat of the musculoskeletal system, increased tolerance to hypoxic loads was revealed.